The Effect of ECG Training Workshop on Medical Students Knowledge of ECG Reading and Interpretation - Navid Omidifar; Nikoo Yamani; Alireza Yousefi (Kerman University of Medical Sciences, 2007)
Background : The importance of adequate training of Medical students in regard to the reading and interpretation of ECG is obvious and there are various studies about new methods of teaching ECG interpretation Objective : This study was aimed to determine the effect of teaching ECG interpretation in workshops and to compare it with current method of ECG training in Isfahan University of Medical Sciences Methods: This experimental study was done on two groups of students using pretest/ posttest design For this purpose 88 Medical students of an academic semester admitted to the university in the same year were selected and randomly divided into two groups of experimental group (taught in the workshop) and control group (taught by the current method) during Internal Medicine Ward Results: In whole 88 students participated in the study of whom 45 were in the experimental group and 43 ones in the control group In the experimental group mean (±SD) scores of the pretest (6 ± 11) and posttest test (17 ± 7) showed a significant difference (p=00001) Mean difference of pre and posttest scores in experimental group was significantly higher than that in the control group (P=00001) Eighty five percent of students in the control group believed on the inefficacy of ECG training in the current educational system while 8380% of participants in the experimental group believed on the efficacy of ECG workshop on their learning Conclusion: Using new educational methods to improve the quality of educational system and to provide some new opportunities for students to learn by more initiative ways are highly necessary The obtained results showed clearly the efficacy of the new method comparing to the current one